A COMPARATIVE STUDY OF PILE BEARING CAPACITY ANALYSIS RESULTS BASED ON THE EMPIRICAL METHOD (STANDARD PENETRATION TEST) AND THE FINITE ELEMENT METHOD - Alfin Reza Saputra Alfin; Dian Purnamawati Solin; Yerry Kahaditu Firmansyah (Jurnal Ilmiah Teknik Sipil, 2024)
This study aims to compare the bearing capacity of steel pile foundations using two approaches: an empirical method based on Standard Penetration Test (SPT) data with Meyerhof’s formula, and a numerical method based on the Finite Element Method (FEM). The research object is a steel pipe pile foundation with a diameter of 850 mm and a depth of 43 meters, used in a port dock structure. Data were obtained from field tests, including bore logs and corrected N-SPT values. The Meyerhof method was applied to manually calculate the end-bearing and shaft friction capacity of the pile, while the FEM approach involved two-dimensional geometric modeling using soil parameters derived from field data and technical assumptions. The analysis results indicate that the Meyerhof method yields an allowable bearing capacity of 7855.23 kN/m², whereas the FEM method results in a capacity of 1432.16 kN/m², with a comparison ratio of 0.1823. This discrepancy suggests that the finite element method provides more conservative and realistic results by thoroughly considering soil-structure interaction. Therefore, the finite element method is recommended for foundation design in large-scale projects or cases requiring high accuracy.